Growth response of Shorea assamica Dyer seedlings to shading leveland growth inhibitor treatments - Arif Irawan; Darwo (Foresty Faculty of Hasanuddin University, 2017)
Shorea assamica Dyer is one of the forest trees with recalcitrant seed type, It can not be stored for long periods. Storage technique of planting material in the form of seedlings is one solution that can be done to overcome the problems of the seeds with a short shelf life. The aim of the research is to determine the growth response of S. assamica seedlings to shading andgrowth inhibitor treatments. Research design was approached by split plot design. The main plot was shade and sub plot was a growth inhibitor. The storage conditions consisted of (1) light (38,600 47,200 lux), (2) medium (19,342 35,300 lux) and (3) heavy shading (62 2,106 lux). The inhibitors used were (1) paclobutrazol 250 ppm , (2) NaCl 0.5% and (3) aquadest (as a control). The results showed that the combined treatment of paclubutrazol 250 ppm with heavy shade was able to suppress the growth of height, dry weight of root and seedling quality index of S. assamica at the age of 6 months optimally in nursery.